Construction and characterization of a spray-ice pad, Tuktoyaktuk, Northwest Territories - Instanes, Arne; Sego, David C.; Addo, Kofi (Canadian Geotechnical Journal, 1994)
During the winter of 1990–1991, a field research program was undertaken to investigate the in situ properties of spray ice, since information on the mechanical and physical properties of undisturbed field-produced spray ice is scarce. The main objective of this research was to retrieve undisturbed field samples for laboratory characterization and to make field measurements to assist in studying the formation processes and physical properties after formation. For this purpose, a spray-ice pad was constructed in the freshwater Tuktoyaktuk Harbour, Northwest Territories, Canada. The 4.3 m thick pad was partly grounded in water depths of 3–6 m and had a maximum freeboard of 2.2 m. The spray-ice pad was constructed using a mobile spray-ice system placed on the first-year ice sheet. The ice production efficiency of the system was measured and found to give an ice content higher than 50%. A total of 11.8 m of cores of nonsaturated undisturbed spray ice were retrieved from three locations on the pad and transported to a cold room facility for density, shear wave velocity, and mechanical behavior testing. In addition, surface wave testing of the in situ spray ice and first-year ice was performed. This paper describes the field study and the methodologies employed to carry out this research. Key words : spray ice, construction, sampling, density, Rayleigh wave velocity.